Challenges in Care and Service Provision for Older Adults with Intellectual Disabilities and Complex Age-Related Conditions in Ireland - Sheerin, Fintan; Fleming, Sandra; Mc Callion, Philip; Mc Carron, Mary (My University, 2024)
Background: People with intellectual disabilities are living longer and are increasingly diverse, with health and care needs that are varied and complex. Without changes to funding, services have found it difficult to respond to needs and wishes. Method: A descriptive mixed methods design study, data were collected through questionnaire, focus groups and individual interviews from intellectual disability service managers, direct care staff and older people with intellectual disabilities and family members. Results: Continued reticence on the part of some community healthcare providers to treat people with intellectual disability was noted. Although some service innovations were noted, housing, staffing levels, staff mix and the timely provision of equipment were all reported to impact the ability of services to respond to changing needs. Current per‐capita funding practices were reported as unresponsive to growing age‐related complexity and fundamentally unsustainable. Conclusions: The health inequalities experienced by people with intellectual disabilities are compounded as they age with complex age‐related health needs. There is an urgent need for revision of the service model in Ireland and instigation of flexible and responsive approaches to funding.
PUBLISHED
Keywords: Health; Research; Intellectual disability